VIKAS MEHTA - The Street, a Quintessential Social Public Space (2014) - Balsas, Carlos J.L. (ZARCH, 2015)
VIKAS MEHTAThe Street. A Quintessential Social Public SpaceRoutledge, New York, 2014, 256 p. English